Evaluation of depressive mood and cognitive functions in patients with acromegaly under somatostatin analogue therapy - YAVUZ, DİLEK; TUNCER, EMİNE NEŞE; ULUÇ, KAYIHAN; KAHRAMAN KOYTAK, PINAR; TANRIDAĞ, TÜLİN (SPRINGER, 2017)
Aims Acromegaly is caused by a pituitary adenoma that releases excess growth hormone (GH) and a concomitant increase in insulin-like growth factor 1 (IGF-1). Acromegaly results not only in phenotypic changes, but also in neurologic complications as peripheral neuropathy and cognitive dysfunction. This study aimed to compare depressive mood and cognitive function in patients with acromegaly and in healthy controls as well as to determine the factors underlying cognitive dysfunction in the acromegalic patients. Materials and methods This study included 42 patients with acromegaly that were receiving somatostatin analogue therapy and 44 healthy controls. Memory, attention, visuospatial function, inhibitory function, abstract thinking, verbal fluency, and depressive mood were measured in the patients and controls. Results Patients with acromegaly had lower learning (p = 0.01), planning (p = 0.03), complex attention and inhibitory function (p = 0.04) scores than the controls. There was no significant difference in depressive mood between the patients and controls (p > 0.05). Gamma knife radiosurgery did not negatively affect cognitive function (p > 0.05). Conclusion The present findings show that acromegaly negatively affects learning, attention, and planning.
Keywords: Acromegaly; Depressive mood; Cognitive functions; QUALITY-OF-LIFE; GROWTH-FACTOR-I; LONG-TERM CURE; PITUITARY-TUMORS; HORMONE EXCESS; RADIOTHERAPY; IMPAIRMENT; BRAIN; COMPLICATIONS; DYSFUNCTION